Geografi Hukum Proyek Strategis Nasional: Studi Kasus Bendungan Bener di Purworejo, Jawa Tengah - Agung Wardana (Fakultas Hukum Universitas Jambi, 2022)
The national strategic projects have been introduced by the Jokowi administration to list several projects that are considered contributing significantly to the nation’s economic growth. Several privileges are given to accelerate the projects including the relaxation of administrative requirements as well as guarantees from financial and political risks. However, as a development project, it is unavoidable that in the implementation they have socio-spatial implications on the ground. This article aims at examining the national strategic project from a legal geography perspective to examine how law works in producing spaces for a new circuit of capital and how spatial justice for local communities living within the spatial unit is implicated. In this regard, a particular attention will be given to the case of the construction of the Bener Dam in Purworejo, Central Java. It argues that the project, including the mining activity in Wadas Village, should be seen as an attempt from the state to produce a space for new circuits of capital, especially for tourism industries. However, such production has created three problems of spatial justice, namely the recognition, participation, and distributive issues. Abstrak Proyek strategis nasional diperkenalkan oleh Pemerintahan Jokowi untuk memasukkan proyek-proyek yang dinilai memiliki kontribusi besar bagi pertumbuhan ekonomi ke dalam satu daftar prioritas. Beberapa keistimewaan pun diberikan untuk melakukan percepatan proyek tersebut termasuk di dalamnya kemudahan dalam pengurusan persyaratan administratif hingga jaminan risiko finansial dan politik. Akan tetapi, sebagai proyek pembangunan, dalam pelaksanaannya tidak dapat dihindari bahwa ia memiliki implikasi sosial-keruangan. Artikel ini bertujuan untuk mengkaji proyek strategis nasional dari perspektif geografi hukum guna membedah bagaimana hukum berperan dalam proses produksi ruang baru untuk sirkulasi kapital dan bagaimana implikasinya terhadap keadilan ruang bagi masyarakat yang mendiami unit ruang tersebut. Dalam hal ini, perhatian akan dikhususkan pada kasus pembangunan Bendungan Bener di Purworejo, Jawa Tengah. Artikel ini berpendapat bahwa proyek pembangunan Bendungan Bener, termasuk penambangan andesit di Desa Wadas di dalamnya, harus dilihat sebagai upaya negara untuk memproduksi ruang sirkulasi baru bagi kapital, utamanya industri pariwisata. Akan tetapi produksi ruang ini telah menciptakan tiga permasalahan keadilan ruang yakni mengenai pengakuan, partisipasi dan distribusi.